Investigating the effects of a range shifter on skin dose in proton therapy - Ming Wang; Lei Zhang; Jinxing Zheng; Guodong Li; Wei Dai; Lang Dong (Nuclear Engineering and Technology, 2023)
Proton treatment may deliver a larger dose to a patient’s skin than traditional photon therapy, especially when a range shifter (RS) is inserted in the beam path. This study investigated the effects of an RS on skin dose while considering RS with different thicknesses, airgaps and materials. First, the physical model of the scanning nozzle with RS was established in the TOol for PArticle Simulation (TOPAS) code, and the effects of the RS on the skin dose were studied. Second, the variations in the skin dose and isocenter beam size were examined by reducing the air gap. Finally, the effects of different RS materials, such as polymethylmethacrylate (PMMA), Lexan, polyethylene and polystyrene, on the skin dose were analysed. The results demonstrated that the current RS design had a negligible effect on the skin dose, whereas the RS significantly impacted the isocenter beam size. The skin dose was increased considerably when the RS was placed close to the phantom. Moreover, the magnitude of the increase was related to the thickness of the inserted RS. Meanwhile, the results also revealed that the secondary proton primarily contributed to the increased skin dose.